PROFIL PENGETAHUAN MASYARAKAT KOTA MANADO MENGENAI ANTIBIOTIKA AMOKSISILIN - Pandean, Friskilia; Tjitrosantoso, Heedy; Goenawi, Lily Ranty (PHARMACON, 2013)
Medicine gives lots of benefits for human being, if it used properly. Improper use of drugscause problem with health, medication failure, even death (WHO, 2004). Antibiotic as drugswhich cure infection must be used correctly. One of antibiotics most used by society isamoxicillin. The aims of this research was to find out how far the knowledge of Manado citysociety about antibiotic especially amoxicillin. This research was descriptive with crosssectional approach. Sampling method were quota sampling namely 150 respondens ofManado city people which divided into three groups : health student, health workers and nonhealth workers. Based on results, Manado city society possess middle knowledge aboutamoxicillin antibiotics by 49,3 %. Most of respondents in health workers group possess highknowledge by 70 %, health student possess middle knowledge by 68 %, and non healthworkers possess middle knowledge by 52 % about amoxicillin antibiotic.Keywords: Antibiotic, Amoxicillin, knowledge